The deliberations of the Municipal People’s Council are a mechanism to establish administrative transparency at the municipal level in Algeria - Boukhenfouf, Soumia; Aouabed, Chahrazed (Milev Journal of Research and Studies, 2022)
The present study aims to know the extent to which administrative transparency is consecrated at the local level in Algeria through the People's Municipal Council deliberations, as it is considered as a place for embodying the values ​​of participatory democracy in local management. This study implies the guarantees of establishing administrative transparency, namely: increasing the number of sessions of the Municipal Council, setting the date and the place of the meeting, the publicity of the sessions, and the drawing up of the closing minutes of the session. However, this initiative has limited effectiveness due to the obstacles limiting its consecration, namely: the legislation of the confidentiality of deliberations as a procedure that contradicts transparency, as well as the unwillingness of local administrators to involve citizens in decision-making policy, in addition to the phenomenon of citizens’ reluctance to attend the council’s deliberations.